ANALYZING DIALOGIC MENTORING FOR DEVELOPING A PRE-SERVICE TEACHER'S CLASSROOM MANAGEMENT PRACTICES - Wibowo, Fachry Ali (2017)
A key concern for pre-service teachers is classroom management, including student behavior management which also has been a factor associated with teachers in general. This study investigates the dialogic mentoring practices used to guide the mentee's classroom management. Using multiple data sources (e.g. pre-service teacher reflections, observer's field notes, video-recorded observations and interviews), this case study uses dialogic mentoring model combined with five-factor mentoring model (Hudson, 2007) in education and the roles of mentor and mentee (Sulzer-Azaroff and Mayer, 1991) to analyze mentor-mentee dialogues in regard to pre-service teacher's development. The participants in this research were two, they were the senior-teacher who acted as the mentor, and the pre-service teacher who acted as the mentee. The mentoring itself was conducted eight times after the class session finished. After the research conducted, it was shown that the mentee could implement the feedback gained from the dialogic mentoring quite well. Every single feedback that she received, she could implement them in the following meetings. The mentor also was pleased to see her mentee's progression because the condition was quite different with the beginning. The mentor also said that she was very satisfied for what the mentee had done. However, all the findings showed that the dialogic mentoring could develop the pre-service teacher. It was seen from the beginning four weeks that the pre-service teacher still had some problems in teaching, but the more she experienced the circumstances of teaching, she could perform some progression and be able to be a better teacher.